2019
DOI: 10.1038/s41586-019-1719-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to commensal papillomaviruses protects against skin cancer

Abstract: Immunosuppression increases the risk of cancers associated with viral infection 1. In particular, squamous cell carcinoma (SCC) of the skin has a >100-fold increased risk in immunosuppressed patients and has been associated with beta human papillomavirus (β-HPV) infection 2-4. Previous studies, however, have failed to establish a causative role for HPVs in driving skin cancer development. Herein, we provide an alternative explanation for this association by demonstrating that the T cell immunity against commen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 23 publications
1
67
0
1
Order By: Relevance
“…However, given the typically transient nature of β-HPV infections, the increased mutational burden may not be particularly consequential. Furthermore, others have suggested that β-HPV infections prime the immune system, helping to prevent NMSCs [ 15 ]. These positions are not mutually exclusive, and should not be interpreted as being in conflict.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the typically transient nature of β-HPV infections, the increased mutational burden may not be particularly consequential. Furthermore, others have suggested that β-HPV infections prime the immune system, helping to prevent NMSCs [ 15 ]. These positions are not mutually exclusive, and should not be interpreted as being in conflict.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it remains unclear if/how frequently β-HPV infections contribute to NMSC. The “hit and run” model faced further challenges when a recent report suggested β-HPV infections protected against NMSC [ 15 ]. The widespread nature of these infections and their contentious role in tumorigenesis are strong motivating factors for ongoing research into the basic biology of the virus and its gene products.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these are phages, but the virome also includes human and animal viruses as well as ERVs and viruses that normally infect plants, archaea and fungi 200,201 . It remains to be understood whether or not viruses can truly be considered commensals given their inherent requirement for replication within host cells, although, when considered from the perspective of a multi-organ system host, viruses can provide benefit by promoting immune development, influencing tissue architecture and promoting immune surveillance against cancer 202,203 . There are multiple animal models and associative human studies in which pathogenic viruses were found to have a role in autoimmunity 158 .…”
Section: Viruses In Autoimmunitymentioning
confidence: 99%
“…In addition, these β-HPVs are also characterized as co-factors, which, in combination with ultraviolet (UV) irradiation, have been thought to contribute to the development of non-melanoma skin cancers (NMSC) [16]. This was later questioned and it was proposed that loss of T-cell immunity, rather than HPV activity, increased the risk of CSCC in immunosuppressed patients [19].…”
Section: Introductionmentioning
confidence: 99%